Re-desain Interior Penampungan Jompo dan Yatim Piatu “Yayasan Cinta Kasih Ibu Teresa” Surabaya - Rebecca Moudy Tanudjaja; Mariana Wibowo; Poppy Firtatwentyna Nilasari (Intra, 2020)
Social home is a social service institution established by the government or the public or private sector, which aims to provide assistance to individuals, community groups in an effort to meet the needs of life. In fact, many social institutions are less concerned with the suitability of a place to live, which in the future can affect the quality of life of its inhabitants. With the problems previously described, the designer provides a solution in the form of a social re-interior design of a social home with a more modern and livable design, supported by universal design features that are expected to help the mobility efficiency of the occupants. The design thinking design method used was adopted by the Hasso-Plattner Institute of Design at Stanford. The five stages of design thinking according to this school are empathize, define, ideate, prototype, and test. The purpose of this design is to make a place to live that is habitable so that the residents feel at home living in the orphanage, facilitate mobility and make them to have the spirits to survive more in living their lives continuously.